The Reality of Crisis Management at Umm Al-Qura University in Light of the COVID-19 Pandemic and its Impact on the University’s Crisis Management Plans - Al-Otaibi, Saad Aziz (The Arab Journal of Administration, 2024)
The current study aims to identify the reality of the crisis management at Umm Al-Qura University in light of the COVID-19 pandemic and its impact on the university’s general plans, the quality of the educational service provided by the university, and to provide service for the community, community partnership and exchange of experiences. meanwhile, the study explains the challenges which the Umm Al-Qura University is facing in light of the current crisis. The research was conducted using a survey method to collect information and data from the study sample, which was randomly selected from the study population consisting of employees and students of Umm Al-Qura University in Makkah Al-Mukarramah region. The results of the statistical analysis showed some results, most notably the approval of the sample members that the reality of crisis management at Umm Al-Qura University in light of the COVID-19 pandemic was great. On the other hand, the approval of the sample members on the quality of the educational service provided by the university was also large. The results also showed the university’s commitment and effective contribution to social responsibility programs in all fields. The study indicated that the most prominent challenges are the lack of qualified human resources administratively and technically at work during crisis management at the university. The study recommended working on making crisis management planning as a part of strategic planning in higher education institutions and focusing on the objectives of Vision 2030, the digital electronic transformation strategy and the requirements of life after the end of the Corona pandemic. In addition, it needs to increase and modernize the use of modern technologies and means of communication currently used at the university; also, to adopt electronic management and to try to keep pace with developments in this regard for its great and fundamental role in the educational process.